The Interior West A Fire Survey - Pyne, Stephen J., 1949- (Book collections on Project MUSE., 2017)
"Surveys the fire scene characteristic of Nevada, Utah, and western Colorado through a mixture of journalism, history, and literary imagination that moves the topic beyond the usual science and policy formulations"--Provided by publisher.